Effects of feeding regime and dietary protein on growth and body composition in Clarias gariepinus (Burchell, 1822) - Ali, M Z; Jauncey, K (Indian Journal of Fisheries, 2011)
Effects of feeding regime and dietary protein on growth and body composition in Clarias gariepinus (Burchell, 1822)